Edukasi Dasar tentang Sebab Kebolehan Mewakilkan Proses Perceraian Kepada Kuasa Hukum - Devi Anugrah Putri (Cendekia, 2022)
Divorce in a marriage relationship is a legal thing according to positive religion and law, but in its implementation it is important to implement some terms and conditions. The purpose of this study is to examine basic education because of the ability to represent divorce to legal counsel according to Islamic law and positive law as well as the similarities, differences and advantages and disadvantages of representing divorce to legal counsel according to Islamic law and positive law. This research method is a literature study with a ushul fiqh approach that refers to the arūriyah theory, some of the literature used is primary sources from the Civil Procedure Code (KUHAP), the Koran and al-Hadith, as well as secondary literature in the form of the book al- Fiqh al-Islami wa Adillatuhu by Wahbah Zuḥailī and Fiqh al-Sunnah by Sayyid Sabiq. The results of this study indicate that according to the guidance of Islamic law, separation from marriage can occur to avoid the bad effects that can occur. Meanwhile, according to positive law, it is related to the low level of community regarding the proceedings in court. Representing the process according to Islamic law can be done only through speech, while according to positive law it cannot be done by speech alone, but formally by using a special power of attorney. The similarities in representing the divorce process include being allowed to use the help of other people or legal counsel. The advantage of appointing a representative in a divorce case is that there will be process and time efficiency, although with the disadvantage of increasing the cost of rental services